Influencia de los juegos didácticos en el aprendizaje de la matemática en estudiantes de educación primaria de la FCEH, UNAP 2017-2018 - Vela Romero, Rafael (2020)
The present study determines the influence of the didactic games in the learning of the mathematics in students of Primary Education of the Faculty of Sciences of the Education and Humanities of the National University of the Peruvian Amazon. The descriptive method of surveys, the historical of primary sources of records and control of procedures of selective manipulation of the sample. The approach was quantitative. The substantive type at a descriptive level of explanatory scope. The non-experimental design of correlation type in a single group, the sample is constituted by 14.71% of the population of 272 students. It is determined that there is a 49% that the didactic games condition the learning of mathematics. The contrast of the hypothesis at a significance level of ?=0.01, of the Rho correlation coefficient of Spearman r=0.7 by the t-Student distribution in the bilateral test with gl=38, finding a high, positive and significant correlation and accepts the hypothesis: The didactic games influence positively and significantly in the learning of mathematics in the students of Primary Education of the Faculty of Sciences of Education and Humanities of the National University of the Peruvian Amazon.